Generalized Robertson–Walker spacetimes — A survey - Mantica, Carlo Alberto; Molinari, Luca Guido (International journal of geometric methods in modern physics, 2017)
Generalized Robertson–Walker spacetimes extend the notion of Robertson–Walker spacetimes, by allowing for spatial non-homogeneity. A survey is presented, with main focus on Chen's characterization in terms of a timelike concircular vector. Together with their most important properties, some new results are presented.